Curriculum Management in Mentari Intercultural School Bintaro - Pratami, Andhyarnita; Sugiarto, Sugiarto; Ahmad, Masduki (International Journal of Elementary Education, 2021)
This study aims to investigate the curriculum management of the Mentari Intercultural School Bintaro elementary school. This study focuses on curriculum management components that will be studied, namely: a. Curriculum planning stage, b. Organizational stage, c. Implementation stage, and d. Curriculum evaluation stage. The research used a qualitative descriptive research method. Data were collected by conducting observations and interviews with school principals, teachers, and the curriculum section representatives. The data obtained were then analyzed according to Milles and Huberman's method, with the stages of data reduction, data presentation, and conclusion drawing. Based on the research results, the Mentari Intercultural School Bintaro elementary school's curriculum management is going well. The management system starts running by planning, coordinating, implementing, and evaluating the curriculum.